Suppression of strawberry root disease with animal manure composts - Millner, P.D; Ringer, C.E; Maas, J.L (Compost science & utilization, 2004)
Compost has been suggested as a nonchemical alternative to methyl bromide (MeBr) for control of root diseases. Its widespread availability and soil improvement properties are appealing to growers, but they need information on its use and effectiveness relative to the control of economically important root diseases in specific crops. Here, we report results from controlled-environment pot studies on the effects of manure composts on two major soilborne diseases of strawberry: red stele (RS) caused by Phythophthora fragariae, and black root rot (BRR), caused by a complex of fungi. Commercially available, on-farm-produced composts, based on either poultry/steer or dairy manure, were incorporated into two different, naturally infested soils at 5, 10, and 20% rates (v/v). Results show that significant control (36-79%) of RS in susceptible cultivar 'Chandler' occurred at all rates and with both types of compost in comparison with the unamended soil. Low rates (5%) of poultry/steer manure compost produced more disease control than equivalent or greater rates (10% and 20%) of dairy manure compost. However, the 20% rate had significantly greater soluble salts content than all other rates. At this 20% rate, root/shoot biomass accumulation and shoot health ratings were relatively low and equivalent to those from unamended soil, despite the improved content of soil organic matter, cation exchange capacity, and soil micronutrient content. The 5% amendment rate of poultry/steer manure compost provided more control than the 10% or 20% rates and more than the 5-20% rates of dairy manure compost. Soluble salts content in amended soils was significantly greater than in unamended soils, especially at 20% rates of poultry/steer compost. Leaf N from all treatments was deficient despite additional weekly supplemental fertilization. This deficiency coupled with increased soluble salt content at 20% poultry/steer compost amendments likely contributed to reduced root/shoot biomass accumulation and overall reduced plant vigor, thus increasing plant susceptibility to disease. In contrast to RS, BRR in all compost treatments was moderate in intensity and equivalent to the unamended soil, with slight but insignificant control at 5 and 10% rates of poultry/steer compost. Overall effects of the two manure compost amendments on BRR were inconclusive because no treatments, including the soil only, exhibited roots with extensive disease symptoms, despite cultural evidence of BRR pathogen colonization, especially by Rhizoctonia fragariae, during the course of this pot study. Effects of compost on appearance of BRR in strawberry should be pursued over a significantly longer time period than used here, possibly in field plots located on naturally infested soils subject to environmental stressors and seasonally realistic fertilization rates, because major BRR symptoms do not appear in the short-term even when fungal pathogens are present in the root.